Growth Curves of Filamentous Fungi for Utilization in Biocatalytic Reduction of Cyclohexanones (Global Journal of Science Frontier Research, 2013)
The growth of filamentous fungal mass in malt extract culture was recorded over 10 days at 32 o C, with the aim of utilizing the mycelium for the biocatalytic reduction of cyclohexanones1-3. Growth curves were obtained for marine fungi (Aspergillus sydowii CBMAI 933, Penicillium miczynskii CBMAI 930 and Trichoderma sp. CBMAI 932) and terrestrial fungi (Rhizopus sp. Cs1 and Aspergillus sp. Pd1), plotted asusing mycelialdry weight. The mycelia of Aspergillus sp. and Rhizopus sp. catalyzed the biocatalytic reduction of cyclohexanones1-3efficiently, when these substrates were added inthe exponential phase of growth at(72 h). The bioreduction of 4-methylcyclohexanone (3) by Aspergillus sp. and Rhizopus sp. yielded preferentially the cis-4-methylcyclohexanol (6), a thermodynamically and kinetically less stable compound. Whole cells of Aspergillus sp. and Rhizopus sp. showed good enzymatic activities in the bioreduction of ketone 1, yielding trans-diol 4.
Keywords: bioreduction; rhizopussp; aspergillussp; biocatalysis; cyclohexanones